Sociocognitive metaphorm - Hill, Kent A. (2006)
This thesis analyses tense and aspect, in particular the Aspect Hypothesis (Salaberry & Shirai 2002; Bardovi-Harlig 2000; Andersen & Shirai 1996) and introduces an approach to teaching it: sociocognitive metaphorm (SCM). Sociocognitive is a combination of sociocultural theory (Lantolf & Appel 1996; Lantolf 2000) and cognitive grammar (Langacker 1987,1991). These theories are compatible because they share the psycholinguistic position that language and language development are conceptually based. Metaphorm is a combination of metaphor and form. Metaphor is central to concept development (i.e., conceptual metaphor). Form refers to grammatical structure. Much of temporal relations are expressed metaphorica1ly and hence metaphor also plays an essential role in the tense-aspect conceptualisation, grammaticalisation and acquisition process.